Fungal Necrotizing Fasciitis of the Left Hemiface with Subsequent Temporomandibular Ankylosis and Eyelid Lymphedema: A Case Report - Akaranuchat, Nutthawut; Lekdaeng, Pattariya; Yongsuvimol, Min; Manorot, Prat (The Thai Journal of Surgery, 2025)
A 35-year-old female presented with progressive swelling and necrosis of the left cheek after sustaining maxillofacial trauma due to a motorcycle accident. Intravenous antibiotic was given, and emergency debridement was performed. Tissue culture showed Aspergillus flavus complex, Acinetobacter baumannii, and coagulase-negative Staphylococci, so her antibiotics were adjusted to amphotericin B, cefoperazone-sulbactam, and fosfomycin. After the infection was improved, her left hemifacial defect was covered with a skin graft. One month later, she developed a gradually diminishing mouth opening and progressive swelling of her left eyelid that completely obscured her vision. Left temporomandibular joint (TMJ) ankylosis and eyelid lymphedema were diagnosed. Preoperative investigations were performed, and the staged surgical reconstruction strategy was developed. After removing the scar tissues and releasing ankylosis, reconstruction was performed using an anterolateral thigh (ALT) free flap, which directly contacted the left eyelid to facilitate lymphatic drainage. Early postsurgical mouth-opening rehabilitation was introduced. Her swollen left eyelids significantly improved thereafter, and the patient could open her mouth freely with an interincisal gap of 3.5 cm. The second operation involved contouring of the flap, smile reconstruction with a Tensor Fascia Lata sling, and partial resection of the left eyelids to reestablish her vision. The patient can now eat without difficulty, and she has favorably reintegrated into society with good mental health.